Environmental consequences of oil production from oil sands. Issue 2 (2nd February 2017) - Rosa, Lorenzo; Davis, Kyle F.; Rulli, Maria C.; D'Odorico, Paolo
Abstract: Crude oil from oil sands will constitute a substantial share of future global oil demand. Oil sands deposits account for a third of globally proven oil reserves, underlie large natural forested areas, and have extraction methods requiring large volumes of freshwater. Yet little work has been done to quantify some of the main environmental impacts of oil sands operations. Here we examine forest loss and water use for the world's major oil sands deposits. We calculate actual and potential rates of water use and forest loss both in Canadian deposits, where oil sands extraction is already taking place, and in other major deposits worldwide. We estimated that their exploitation, given projected production trends, could result in 1.31 km 3 yr −1 of freshwater demand and 8700 km 2 of forest loss. The expected escalation in oil sands extraction thus portends extensive environmental impacts. Key Points: Oil production from oil sands is of growing importance to the global energy mix The environmental impacts of this production remain poorly understood We assess historical and projected forest loss and water demand Local impacts of oil sands exploitation may be substantial for forests and water resources